Dualisme Pengetahuan Agama: Dinamika Religiusitas Siswa Muslim di SD Kristen Purbo - Muhammad Khoiruzzadi; Lia Dwi Tresnani; Nadia Fitria Khairunisa (Research Institute and Community Engagement of IAIN MADURA, 2022)
Every child has the right to receive religious subjects that he adheres to. When children get different religious subjects, it will become a dualism of understanding in religion. The purpose of this study was to explain the dynamics of religiosity of Muslim students at Purbo Christian Elementary School. This research includes field research using a qualitative method approach. The subjects of this study were 7 Muslim students in grades 4 to 6, parents of Muslim students, classroom teachers, and the principal of SD Kristen Purbo. Methods of data collection using interviews, observation, and documentation. Data analysis by means of data reduction, data presentation, and conclusions. The results showed that the religiosity of Muslim students at Purbo Christian Elementary School was still the same in general, Muslim students who were adjusted to their development, such as still finding it difficult to pray fardu prayers, and still being egocentric. Children will be more interested in annual worship, such as fasting in Ramadan, Islamic holidays. In addition, children are also more interested in religious activities that are collective and entertaining for children. (Setiap anak berhak mendapatkan mata pelajaran agama yang dianutnya. Ketika anak malah mendapatkan mata pelajaran agama yang berbeda, maka akan menjadi dualisme pemahaman dalam konsep beragamanya. Tujuan penelitian ini adalah untuk menjelaskan dinamika religiusitas siswa Muslim SD Kristen Purbo. Penelitian ini termasuk penelitian lapangan dengan menggunakan pendekatan kualitatif. Subjek penelitian ini adalah 7 siswa Muslim kelas 4 sampai kelas 6, orang tua siswa Muslim, guru kelas, dan kepala sekolah SD Kristen Purbo. Metode pengumpulan data dengan menggunakan wawancara, observasi, dan dokumentasi. Analisis data dengan cara reduksi data, penyajian data, dan kesimpulan. Hasil penelitian menunjukkan bahwa religiusitas siswa Muslim SD Kristen Purbo masih sama pada umumnya siswa Muslim yang disesuaikan dengan perkembangannya, seperti masih sulitnya untuk ibadah salat fardu, dan masih bersikap egosentris. Anak akan lebih tertarik dengan ibadah yang sifatnya tahunan, seperti puasa Ramadan, hari raya kebesaran Islam. Selain itu, anak juga lebih tertarik pada kegiatan keagamaan yang sifatnya kolektif dan menghibur bagi anak.)